PENGARUH MEDIA SOSIAL DAN REKOMENDASI SELEBGRAM TERHADAP KEPUTUSAN PEMBELIAN DENGAN EWOM SEBAGAI PEMEDIASI PADA PENGGUNA SHOPEE DI BANDA ACEH - Ajrina Salsabila; Nurdasila Nurdasila (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
This study aims to examine the effect of Social Media and Celebrity Recommendations on Purchase Decisions with Electronic Word of Mouth (e-WOM) as a mediator for Shopee users in Banda Aceh. The sample used in this study were 168 Shoppe users using non-probability sampling technique. Then, this study used data collection equipment, namely a questionnaire (questionnaire). This study uses Hirarchical Lineal Modeling (HLM) as an analytical method to determine the effect of the variables involved in mediation testing in this study. Based on the results of the HLM analysis, it shows that social media has an effect on E-wom, Selebgram Recommendations have an effect on E-wom, Social Media has an effect on Purchase Decisions, Selebgram Recommendations have an effect on Purchasing Decisions, E-wom has an effect on Purchase Decisions, Social Media has an effect on Purchase Decision with E-wom as a mediating variable, and Selebgram Recommendations affect the Purchase Decision with E-wom as a mediating variable.Social Media, Celebrity Recommendation, E-wom, Purchase Decision, Hirarchical Lineal Modeling (HLM)